2006
DOI: 10.1111/j.1742-6723.2006.00807.x
|View full text |Cite
|
Sign up to set email alerts
|

When benzodiazepines fail: How effective is second line therapy for status epilepticus in children?

Abstract: Standard second line anticonvulsant treatment was relatively ineffective in terminating seizures in children who presented in CSE not responsive to benzodiazepines. Failure to respond to prehospital treatment and prolonged seizure duration at presentation both predict poor therapeutic response. Third line treatment with RSI of anaesthesia is often delayed while waiting for second line treatment to work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 16 publications
0
39
1
3
Order By: Relevance
“…In larger studies of critically ill children with heterogeneous acute encephalopathy etiologies, EEG seizures occur in 10–40% of monitored patients, and there is increasing evidence that high seizure burdens are associated with worse outcomes (25). Furthermore, status epilepticus treatment delays are associated with reduced medication efficacy for status epilepticus termination (6, 7). The majority of EEG seizures in critically ill children have no clinical correlate and therefore detection requires EEG monitoring (2, 5, 815).…”
Section: Introductionmentioning
confidence: 99%
“…In larger studies of critically ill children with heterogeneous acute encephalopathy etiologies, EEG seizures occur in 10–40% of monitored patients, and there is increasing evidence that high seizure burdens are associated with worse outcomes (25). Furthermore, status epilepticus treatment delays are associated with reduced medication efficacy for status epilepticus termination (6, 7). The majority of EEG seizures in critically ill children have no clinical correlate and therefore detection requires EEG monitoring (2, 5, 815).…”
Section: Introductionmentioning
confidence: 99%
“…Its reported efficacy is 15% [8,26]-55.8% [43], the latter when administered with a benzodiazepine. Phenobarbital is also an effective second-line agent [43][44][45] and might be of additional benefit if cerebral oedema is a contributing factor [44].…”
Section: Second-line Agentsmentioning
confidence: 98%
“…Current treatment protocols reflect the urgency of CSE and recommend that treatment should be given if a tonic-clonic seizure has lasted for 5 min [5,6]. There is evidence that seizures lasting longer than 30 min are unlikely to stop without intervention [7][8][9], and that prolonged ictal activity, whether or not it is associated with continued clinical (and specifically motor) seizures, causes excitatory amino-acid neurotoxicity-mediated death [10,11] Refractory convulsive status epilepticus (RCSE) may be associated with significant mortality and morbidity [10]. It is less common than CSE and is relatively poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…However, based on the VA Cooperative Study [10] observation that only 7% of patients who failed lorazepam responded to phenytoin as the second drug, some investigators have suggested that the patient should be considered to be in refractory SE if the initial benzodiazepine fails to stop the ongoing seizure activity or prevent recurrent seizures [121]. Duration of seizure activity has also been suggested as a criterion for refractory SE, but the range of times varies between no time requirement and persistence >2 h. Based on these variable definitions, refractory SE has been reported to occur in 10-70% of adults [10,39,40,122] and children [79,123,124] who present with SE.…”
Section: Definition Of Refractory Sementioning
confidence: 99%